Health Care Seeking Behavior of Orofacial Pain on Female in Different Socioeconomic - Risqa Rina Darwita; Peter Andreas; Febriana Setyawati; Iwani Amalliah (Faculty of Dentistry, Universitas Indonesia, 2015)
Objective: The aim of this study was to analyze the health care seeking behavior of orofacial pain on female in different socioeconomic condition. Methods: The sampling was multistage cluster random sampling in 328 female adults who lived in Central Jakarta. The association between variables of socio-economy and health care seeking behavior was analyzed using Kruskal-Wallis test. Results: The results were indicated that education factor had a significant correlation with health care seeking behavior (p<0.001). Socio-economic condition was also significantly correlated to health care seeking behavior (p<0.01). Conclusion: This study was concluded that the female adult with good education and social-economic condition have good behavior on health care seeking treatment for orofacial pain.